Musical exposures and creativity among music major trainee teachers in Malaysia / Lim Zek Chew - Lim, Zek Chew (2014)

(untitled)
The primary purpose of this study was to investigate the relationships between musical exposures and creativity among the pre-service music major trainee teachers from the teacher education institutions in Malaysia. This study also sought to examine the nature of musical creativity and general creativity. Individual differences such as gender, ethnicity, academic years, and socioeconomic status were examined to investigate to what extent these differences moderate the relationships between musical exposures and creativity. In addition, this study also determined the predictors of musical creativity and general creativity In this study, musical exposures were investigated by looking at four aspects namely keyboard grades, musical activity involvement, aural discrimination, and self-esteem of musical ability. Meanwhile, creativity was examined by using two constructs which were musical creativity and general creativity. To address the purposes of the study, quantitative data were collected using a survey approach. As the research questions concerned the relationships between musical exposures and creativity, a correlation design was adopted. The respondents of the study were 159 pre-service music major trainee teachers randomly selected from seven teacher education institutions in Malaysia. In total there were 51 males and 108 females. The dependent variables of this study were musical creativity and general creativity. The independent variables were personal variables and musical exposures. Data for dependent variables were collected using two instruments, namely the Torrance Test of Creative Thinking, and the Composition Test. Data for independent variables were collected from demographic questionnaire, musical activity involvement iv questionnaire, self-esteem of musical ability questionnaire and the Aural Discrimination Test. Descriptive statistics were used to ascertain musical exposures and the nature of creative abilities of the trainee teachers. Inferential statistics were used to ascertain the relationships between musical exposures and creativity. One-way ANOVAs and Tukey HSD were performed to determine significant differences between variables and Pearson Product-Moment correlation were used to analyse the correlations between variables. Besides that, stepwise multiple regression analysis and hierarchical multiple regressions analysis were used to determine the predictors of musical creativity and general creativity. Based on the results of this study, it was concluded that male trainee teachers were more creative in musical creativity than female trainee teachers. However, there was no significant difference between genders in general creativity. Findings of the study also showed that musical exposures influenced musical creativity. Musical creativity were significantly related to musical activity involvement (r = 19, p  .05), aural discrimination (r = 48, p  .05) and self-esteem of musical ability (r = 31, p  .05). On the contrary, musical exposures were not related to general creativity. Stepwise multiple regression analysis revealed that aural discrimination is the strongest predictor of musical creativity, which alone accounted for 29.0% of the variance in total. Subsequently, self-esteem of musical ability is modest in predicting musical creativity. Surprisingly, musical activity involvement did not appear to contribute to musical creativity. As for general creativity, all the variables in musical exposures were not predictor of general creativity.